A Population-Based Analysis of Intraoperative Cardiac Arrest in the United States. (March 2020) - Fielding-Singh, Vikram; Willingham, Mark D.; Fischer, Matthew A.; Grogan, Tristan; Benharash, Peyman; Neelankavil, Jacques P.
Abstract : BACKGROUND: A new billable code for intraoperative cardiac arrest was introduced with the International Classification of Diseases, Tenth Revision, classification system. Using a national administrative database, we performed a retrospective analysis of intraoperative cardiac arrest in the United States. METHODS: Hospital admissions involving patients ≥18 years of age who underwent operating room procedures in 2016 were identified using the National Inpatient Sample. The primary outcome was the incidence of intraoperative cardiac arrest. Secondary outcomes included total cost of admission, in-hospital mortality, length of stay, and identification of risk factors associated with intraoperative cardiac arrest. Clinical risk factors were evaluated with multivariable logistic regression models using sampling weights and adjustment for clustering by strata. RESULTS: Of 35, 675, 421 admissions in 2016 in the United States, 9, 244, 861 admissions were identified in patients ≥18 years of age who underwent at least one operating room procedure. An estimated 5230 hospital admissions involved intraoperative cardiac arrest, yielding an estimated incidence of 5.7 (95% confidence interval [CI], 5.3–6.0) per 10, 000 hospital admissions. Admissions involving an intraoperative cardiac arrest had a 35.7% in-hospital mortality, compared with 1.3% for admissions without intraoperative cardiac arrest. Intraoperative cardiac arrest was associated with a 15.44-fold (95% CI, 12.74–18.70; P < .001) increase in the risk-adjusted odds of in-hospital mortality and an additional 13, 184 (95% CI, 9600–16, 769; P < .001) of total admission costs. Selected factors independently associated with increased risk-adjusted odds of intraoperative cardiac arrest included: black or missing race; cardiac, thoracic, or vascular surgery; congestive heart failure; pulmonary circulation disorders; peripheral vascular disease; end-stage renal disease; and fluid and electrolyte disorders. CONCLUSIONS: In this population-based study of intraoperative cardiac arrest in the United States, admissions involving an intraoperative cardiac arrest were rare but were associated with high in-hospital mortality.